Metode Tafsir (al-Tafsir al-Tahlili, al-Ijmali, al-Muqaran dan al-Mawdu’i) - Anandita Yahya; Kadar M Yusuf; Alwizar Alwizar (PALAPA, 2022)
Tafsir is one way to find out and show the meaning and intent according to the content of the verses of the Qur'an. The purpose of this research is to reveal what methods can be used in interpreting the Qur'an. The research method used is library research. The tafsir methods used by mufassir on the interpretation of the Qur'an can be grouped into four methods; First, the method of ijmali interpretation. Second, the method of tahlili interpretation. Third, the maudhu`i interpretation method. Fourth, the method of interpretation of muqaran. The division of this category is a new categorization, because this category exists after research in various commentary books, as a result, experts in science divide the method of interpretation used by interpreters as 4 kinds. The four interpretation methods commonly used by the mufassir, each have advantages and disadvantages. Although the methods of interpreting the Qur'an are different, the essence remains the same, namely the mufassir trying to explain the meaning of the verses of the Qur'an for themselves and others.